Vaccine temperature management in Lao People's Democratic Republic: A nationwide cross-sectional study. Issue 6 (June 2021) - Kitamura, Tomomi; Bouakhasith, Viraneth; Phounphenghack, Kongxay; Pathammavong, Chansay; Xeuatvongsa, Anonh; Kobayashi, Akiko; Norizuki, Masataro; Okabayashi, Hironori; Miyano, Shinsuke; Mori, Yoshio; Takeda, Makoto; Sugiyama, Masaya; et al.
Abstract: Objective: The objective of the study was to evaluate the duration and frequency of vaccine exposure to suboptimal temperatures during transit from the central vaccine storage in the capital to health centers in Lao PDR. Methods: Temperature data loggers traveled from the capital to the health centre storages (146) with the vaccines to monitor the vaccine temperature nationwide. One health centre per district was selected using a simple random sampling method for the first round of temperature monitoring. One health centre was selected from every forty-nine high risk districts monitor the trend of vaccine temperature at the health centre storage and during outreach sessions in several districts. Vaccines and temperature data loggers were transported using the normal vaccination transportation. Findings: Overall, the vaccines were exposed to temperatures >8 °C for an average of 1648 min, equivalent to 9.0% of the observational period, and to temperatures <0 °C for an average of 184 min, equivalent to 1.35% of the study period. The proportion of exposure to temperatures >8 °C was the highest during the transit from the capital to the province. The proportion of exposure to temperatures <0 °C was the highest during storage at district level. Examined by region, vaccines in the northern provinces had higher risk of exposure to temperatures >8 °C; however, the risk of exposure to temperatures <0 °C was scattered nationwide. Moreover, some health centers showed fluctuations in storage temperature. Conclusions: Challenges associated with cold chain management, and the resulting deterioration of vaccines, might account for outbreaks of vaccine-preventable diseases. The government should examine and invest in suitable technologies and approaches to ensure consistency in cold chain management. Highlights: The Lao PDR has suffered several outbreaks of vaccine-preventable diseases. This study investigated the cold chain during vaccine transport to health centres. Vaccines were exposed to suboptimal conditions during transit from central to health centres and at storage at all levels. Vaccine storage temperature fluctuated in some health centres. Deficiencies in cold chain management may contribute to outbreaks of vaccine-preventable diseases. Abstract : Cold chain; Expanded program on immunization; National immunization program.